2020
DOI: 10.2196/25117
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as ‘Game Changer’ for the Physical Activity and Mental Well-Being of Augmented Reality Game Players During the Pandemic: Mixed Methods Survey Study

Abstract: Background Location-based augmented reality (AR) games, such as Pokémon GO and Harry Potter: Wizards Unite, have been shown to have a beneficial impact on the physical activity, social connectedness, and mental health of their players. In March 2020, global social distancing measures related to the COVID-19 pandemic prompted the AR games developer Niantic Inc to implement several changes to ensure continued player engagement with Pokémon GO and Harry Potter: Wizards Unite. We sought to examine how … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 48 publications
5
82
1
6
Order By: Relevance
“…Most cities in Hubei Province were also quarantined, restricting people from traveling out of their own cities. People in proximity can easily transmit COVID-19; thus, social (ie, physical) distancing is an important measure to reduce its spread [ 4 ]. By February 2020, China had introduced travel bans and quarantine measures, closed public services, and canceled social events to contain COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Most cities in Hubei Province were also quarantined, restricting people from traveling out of their own cities. People in proximity can easily transmit COVID-19; thus, social (ie, physical) distancing is an important measure to reduce its spread [ 4 ]. By February 2020, China had introduced travel bans and quarantine measures, closed public services, and canceled social events to contain COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this started with behavioral segmentation of two explicit groups consisting of casual and hardcore players [19,24]. This casual/hardcore binary is also expanded upon in the game literature to provide a more comprehensive player behavioral range by including both mid-core players (that lie in-between the two extremes of casual and hardcore players) [12,29], and those who are yet to establish any type of player identity (no-identification) [12,27,30].…”
Section: Segmentation Theorymentioning
confidence: 99%
“…The authors also highlight that PGO can be integrated into a daily commute, and during other travels, and have the potential to provide other health-related benefits, such as social well-being [18]. More recently, Ellis et al [12] identified that HPWU and PGO exergames have the potential to promote physical and mental health during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations